Exposure to Dibutyl Phthalate and Reproductive-Related Outcomes in Animal Models: Evidence From Rodents Study - Wang, Jiawei; Zhang, Xi; Li, Yang; Liu, Yingqing; Tao, Lingsong (Frontiers in Physiology, 2021)
Background: Dibutyl phthalate (DBP) was an endocrine disruptor, which may lead to cancer and affects reproductive function when accumulated in the body. But the precise role of DBP in the reproductive system remained controversial. Objective: We employed the meta-analysis to explore the relationship between DBP and reproductive-related outcomes. Methods: We searched relevant literature in PubMed, EMBASE, and Web of Science databases. The standardized mean differences (SMDs) and their 95% CIs were measured by random-effects models. Funnel plots and Egger’s regression test were applied to assess publication bias. Results: Finally, 19 literatures were included in this research. The outcomes revealed that DBP was negatively correlated with reproductive organs weight (testis weight: SMD: −0.59; 95% Cl: −1.23, −0.23; seminal vesicles weight: SMD: −0.74; 95% Cl: −1.21, −0.27; prostate weight: SMD: −0.46; 95% Cl: −0.76, −0.16) and sperm parameters (sperm morphology: SMD: 1.29; 95% Cl: 0.63, 1.94; sperm count: SMD: −1.81; 95% Cl: −2.39, −1.23; sperm motility: SMD: −1.92; 95% Cl: −2.62, −1.23). Conclusion: Our research demonstrated that DBP may be negatively associated with reproductive-related indicators, especially at Gestation exposure period and middle dose (100–500 mg/kg/day).